"The fouled player should not take the penalty himself": An empirical investigation of an old German football myth - Kuss, O.; Kluttig, A.; Stoll, O. (Journal of Sports Sciences, 2007)
In this study, we investigate the old German football myth that the fouled player should not take the resulting penalty himself, as he is at an increased risk of missing. Previous analyses are improved on as we adjust for potential confounders that might influence self-taking as well as successful penalty conversion. Our findings reveal some important predictors for self-taking but, somewhat surprisingly, neither self-taking nor any of the potential confounders predicts scoring a penalty kick.